Barrier functions for one class of semilinear parabolic equations - Bondarenko, V. G.; Prokopenko, Yu. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
For a parabolic quasilinear equation with monotone convex potential, we construct superparabolic and subparabolic barrier functions by the method of decomposition.